Was the early food the late poison? Foreign banks and the retail credit market during Ireland's financial crisis - Frost, Sarah; Goggin, Jean; O'Brien, Martin (Statistical and Social Inquiry Statistical Society of Ireland, 2015)
Ireland's banking system is among the most open in the world, with a significant amount of the industry headquartered in other countries. In this paper we examine the development of the industry in the run up to the recent domestic and international financial crises. We highlight the three distinct categories of banks operating in Ireland, which allows for a more accurate analysis of the interaction of the banking system with the domestic economy. Focussing specifically on the retail market, we analyse the role of foreign ownership in determining how banks responded to the domestic and international crises through their provision of credit to the Irish non-financial private sector. We find a significant role for parent group liquidity and conditions related to recapitalisation by home country governments in explaining the difference between credit growth during the crisis for foreign and Irish-owned banks. The potential for EU policy developments to avoid such differences in future crises is explored.
(read before the Society, 5th March 2015)
Keywords: credit; Ireland; banking union; multinational banks; 314.15